PENERAPAN PASAL 106 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN TERHADAP PENGGUNA SEPEDA MOTOR DI WILAYAH KECAMATAN MERBAU - Desyi Cristin Natalia; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In Indonesian law has been very clearly regulated about the behavior of traffic,but in fact today what happens in the field is not in accordance with the aspirations ofthe legislation. Based on this fact, then there are three formulation problems inwriting this thesis, ie: First How is the application of Article 106 of Law Number 22Year 2009 on Road Traffic and Transportation to Motorcycle Users in Merbau Subdistrict?,secondly how is the role of the Police in the application of Article 106 ofLaw Number 22 Year 2009 on Road Traffic and Transportation to Motorcycle Usersin Merbau District?,third, what are the obstacles in the application of Article 106 ofLaw Number 22 Year 2009 on Traffic and Road Transport in Merbau Sub-district?.The research method in this research is qualitative research method withempirical juridical approach or sociological law research. Data sources aresupported by primary and secondary data sources. Data collection techniques usedwere interviews, questionnaires and literature review. After the data collected thenanalyzed qualitatively, and draw conclusions with the deductive thinking method ofanalyzing the problem from the general shape to the special form.From the results of research and discussion it can be concluded that, with noUnitlantas in Merbau Sector Police, the Implementation of Article 106 of the Law onTraffic and Road Transport will not be in accordance with what is aspired by law,which is an important role in carrying out the task of securing traffic is the task ofUnitlantas. So far, traffic security in Merbau sub-district is handled directly by theMeranti Islands Resort Police Traffic Unit, but since access to every sub-district mustpass through the sea and the means of transportation is only speedboat, theperformance of Satlantas itself is not effective. The obstacles of law enforcement arethe lack of professional elements of the apparatus, the lack of public understandingabout the law and the lack of public awareness to comply with applicable law. Someefforts are made to overcome these obstacles by providing legal counselingconducted in first to senior high school and socializing to the general public, andimproving the police ability in the application of legislation.Keywords: Law Enforcement-Traffic-offenses